Basic Provisions of Noospheric Education in the Context of Modern Civilization Paradigm - Terentieva, Nataliia; Yashnik, Svitlana (Journal of Education, Technology and Computer Science, 2019)
The main idea of sustainable development of society is the formation of a holistic ecological, Noosphere worldview, and formation of a holistic Noosphere consciousness, the components of which are integral thinking, ethical bio-adequate method of behavior (ecological ethics) and ecological worldview are defined as the main goal of Noosphere education.